Critical Analysis of Newspaper Fiction from Union Press, Nanyang Zonghui Xinbao - Kow , Mei-Kao (Recent Research Advances in Arts and Social Studies Vol. 5, 2024)
The local newspapers had baihua (colloquial) articles or fiction in their supplements even before 1911 but were comparatively limited in number. After 1919, a great number of newspaper supplements/magazines in the Chinese Mainland in the same period adopted baihua as a medium of expression. What we can expect for fiction from the Union Press in this period 1924-1928 under study was my primary concern when I carried out my research of fiction from the Union Press from 1917 to 1923. Contrary to my expectation, new political developments that took place in the Chinese Mainland coupled with economic decline in Malaya affected the production of Singapore Chinese fiction writing; language change in the Sinophonic world plus the pressures from local newspaper competitors aggravated the sharp situation. In referring to tales of ghosts and foxes, surprisingly in this period under study, Liaozhai and Pu Songling were vividly associated. The Liaozhai imitation carried on with some innovations in scope, especially the fresh appearance of the plot of the black fox and its fur. Other rare demons such as Morning Glory and banana demons are included. It appears that the intention in publishing these stories changed from asserting belief to drawing attention to these parapsychological phenomena. As they are mythological and religious in nature, it legitimatizes the author of this paper to discuss them separately. Since the linguistic styles of wenyan and baihua by that time were getting closer, the emergence of more baihua stories signalled that a new scenario was about to emerge although lagging slightly behind. The wenyan fiction is more traditional or historical, while baihua stories are more contemporary with modern writing techniques. With Lin Qinnan’s translations of Western fiction into wenyan, the gap between wenyan and baihua fictional writings is somewhat narrowed. So, it is logical to consider both forms together for discussion. The majority of stories are about love and marriage, including cross-racial marriages (although these are limited in number). Tragedies often occurred as new women clashed with traditional ethical thinking. War fiction which condemned the cruelty of fighting and disclosed human nature is touching as well. The editors shared their efforts in organizing the stories so that enhancement of meanings could be achieved. This is reflected in the affiliated information published here and there with an intention to explain, e.g., martial skills stories reflected the need for self-defence in all walks of life in the then chaotic China and overseas Chinese communities. The Union Press somehow carried on its innovative spirit in this period. Its innovation extended to some advertisements, which are significant in terms of art and theme. The classification of genre and sub-genre was meticulously rigid all along; after the disruption of the North Expedition, most classifications were abolished and some of the congtan or small talk columns were opened up to include foreign matters, as a result blurring certain distinctions.